2013
DOI: 10.1007/s00431-013-1988-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired endothelial function in female adolescents with type 1 diabetes measured by peripheral artery tonometry

Abstract: The RH-PAT technique is used as a non-invasive test to assess for early vascular changes in high-risk patient groups. Endothelial dysfunction, measured by RH-PAT, was present in diabetic adolescent, especially in the female subgroup. Although additional longitudinal studies are required, early detection of this reversible process may have therapeutic and prognostic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
(36 reference statements)
3
22
0
Order By: Relevance
“…To our knowledge, differences in baseline pulse amplitude in obese adolescents have not been previously reported. Our group, however, described similar findings in adolescents with type 1 diabetes, with significantly higher baseline pulse amplitude in the diabetes group vs. the control group (8). These findings were consistent with the data from the study of Hamburg et al in adults (7).…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, differences in baseline pulse amplitude in obese adolescents have not been previously reported. Our group, however, described similar findings in adolescents with type 1 diabetes, with significantly higher baseline pulse amplitude in the diabetes group vs. the control group (8). These findings were consistent with the data from the study of Hamburg et al in adults (7).…”
Section: Discussionsupporting
confidence: 92%
“…When comparing the values of measured AW characteristics in patients with diabetes mellitus type 1 with those of age-matched controls, it was found, as in other studies (12)(13)(14)(15) that patients with diabetes type 1 have impaired functional and structural AW characteristics. It seems that the changes of AW characteristics start to occur early in the disease course and slowly progress, finally leading to macrovascular complications.…”
Section: Control Group Treatment Groupsupporting
confidence: 66%
“…Our study used the Endopat device to evaluate the endothelial function in T1DM, T2DM and NDM obese children and adolescents. Previous studies done in children and adolescents with diabetes are mainly in T1DM patients (7,10,(14)(15)(16)(17). Prospective studies with the EndoPAT on T1DM adolescents revealed the presence of endothelial dysfunction in 76.7% (7), and a negative correlation between endothelial function and A1C (10).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that children with T1DM had significant ED when compared with non-diabetics (16,17).…”
Section: Discussionmentioning
confidence: 99%